2019
DOI: 10.1111/imm.13132
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronate rescues immunosuppressed monocytes in sepsis patients

Abstract: Summary Severe sepsis is often accompanied by a transient immune paralysis, which is associated with enhanced susceptibility to secondary infections and poor clinical outcomes. The functional impairment of antigen‐presenting cells is considered to be a major hallmark of this septic immunosuppression, with reduced HLA‐DR expression on circulating monocytes serving as predictor of mortality. Unconventional lymphocytes like γδ T‐cells have the potential to restore immune defects in a variety of pathologies includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Sepsis is a systemic inflammatory response syndrome caused by infection and is one of the leading causes of death worldwide (1)(2)(3). It is a complex disease characterized by severe systemic inflammation and multiple organ dysfunction (e.g., blood vessels, lungs, liver, kidneys, heart, and brain) due to the host's unregulated response to infection (4,5). Multidrug-resistant bacteria, drug side effects and adverse events make the treatment of sepsis considerably complex (2,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is a systemic inflammatory response syndrome caused by infection and is one of the leading causes of death worldwide (1)(2)(3). It is a complex disease characterized by severe systemic inflammation and multiple organ dysfunction (e.g., blood vessels, lungs, liver, kidneys, heart, and brain) due to the host's unregulated response to infection (4,5). Multidrug-resistant bacteria, drug side effects and adverse events make the treatment of sepsis considerably complex (2,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 28 , 29 Furthermore, the reduction of mHLA-DR was demonstrated to be an independent risk factor of nosocomial infection and mortality. 30 In previous studies conducted in AP patients, a reduced proportion of mHLA-DR in the early stage was associated with increased disease severity, development of secondary infection, or decreased survival, raising an association between immunosuppression and poor in-hospital prognosis. 3–9 Early in 2004, Mentula et al 4 have studied 74 patients with acute pancreatitis (AP) admitted within 72 h after symptom onset and found that a reduced proportion of mHLA-DR was associated with secondary infection of pancreatic necrosis.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 77 patients were enrolled between 2018 and 2021 who were over 18 years old with a diagnosis of sepsis according to the Third International Consensus Definitions for Sepsis and Septic Shock (‘Sepsis-3’) [45]. They were cared for in the intensive care unit at the University Hospital of Wales in Cardiff, and were recruited within 36 hours of the presumed onset of infective illness when they already had or would require arterial cannulation as part of standard treatment [46]. Patients were excluded if they were pregnant or breastfeeding, or were females of childbearing age in whom a pregnancy test had not been performed; had severe immune deficiency ( e.g.…”
Section: Methodsmentioning
confidence: 99%